Allelic ratio of KRAS mutations in pancreatic cancer - Lennerz, Jochen K.; Stenzinger, Albrecht (The oncologist, 2015)
KRAS is not simply mutated or wild type in pancreatic ductal adenocarcinoma (PDAC); actually, it has never been. More than 90% of PDACs carry mutated KRAS alleles; however, the impact on PDAC biology may vary with the tumor-specific allelic ratio and dosage of mutated KRAS.